Pengujian Performa, Tingkat Stres, dan Keamanan Pada Website Sekolah Menengah Atas Negeri (SMAN) Kabupaten Buleleng - Varelly Arletta Tyora Putri Herlambang; I Made Edy Listartha; Bagus Gede Krishna Yudistira (Jurnal Publikasi Teknik Informatika, 2026)
The use of information technology in the education sector has become an unavoidable necessity, particularly through the use of school websites as digital information service centers for students, teachers, parents, and the general public. School websites serve not only as a medium for conveying information but also as a means of communication, transparency, and support for academic activities. To optimally fulfill these roles, a website must be able to deliver good performance, fast access, high stability when there is an increase in the number of visitors, and adequate security to protect user data and activities. In Buleleng Regency, 17 state senior high schools (SMAN) have utilized official websites as part of their information services and digital administration needs. However, increased traffic, especially during certain times such as new student admissions or school announcements, often triggers high workloads (stress) on servers. This condition has the potential to reduce response speed, hinder user access, and even open up opportunities for security threats such as DDoS attacks and hacking attempts. This study aims to evaluate the technical performance, load resilience, and security aspects of the websites of senior high schools in Buleleng Regency using three automated testing tools: GTMetrix, LoadImpact K6.io, and OWASP ZAP Scan. This approach draws on previous research on website performance measurement, load testing, and user experience. The evaluation results are expected to provide a comprehensive overview of the actual condition of school websites and generate strategic recommendations to improve system speed, stability, and security. Furthermore, the findings from this testing serve as a basis for developing improvement measures so that school websites in Buleleng Regency can support digital education services more optimally, responsively, and securely.